Analysis on in‐band distortion caused by switching amplifiers. Issue 5 (1st April 2014) - Jang, Wonhoon; Silva, Nelson; Oliveira, Arnaldo; Carvalho, Nuno Borges
Abstract : A hypothetical model is built to explain an in‐band distortion mechanism of the class F amplifier. Using the model it is analytically proved that static non‐linearities of switching amplifiers do not cause meaningful in‐band distortion when the amplifiers are driven by ideal 1‐bit digital RF signals. It is also found that short‐term memory effects significantly contribute to in‐band distortion. The analysis and the mechanism are tested and supported by MATLAB simulations. A system composed of a field‐programmable gate array and a class F amplifier has been built and the in‐band distortion mechanism is verified by measurement.